Pola Penggunaan Obat Diare Akut Pada Balita di Rumah Sakit - Sofia Futria Wulandari; Muhammad Akib Yuswar; Nera Umilia Purwanti (State University of Gorontalo, 2022)
The prevalence of diarrhea in Indonesia based on the diagnosis of health workers reached 6.8% in 2018. Generally attacks toddlers under the age of 5 years because the toddler's immune system is still in the weak category, making them more susceptible to exposure to bacteria that cause diarrhea. The most cases of diarrhea in Indonesia are cases of acute diarrhea. This study aims to determine the pattern of use of acute diarrhea medication in toddlers at Sultan Syarif Mohamad Alkadrie Hospital Pontianak in 2020. This study used a descriptive observational method with a cross-sectional research design. Retrospective data collection using purposive sampling method. The results showed that the characteristics of patients by gender who suffered the most from acute diarrhea were women (55%), the most age group was 0-1 year (30%), the type of diarrhea that most suffered was acute diarrhea without dehydration (51, 25%) and the most felt clinical symptoms were liquid defecation and fever (44.20% and 20.99%). The most widely prescribed drug to treat acute watery diarrhea was zinc (27.97%). The conclusion in this study is that the most widely prescribed drug to treat acute diarrheal disease in toddlers is zinc.